Kontribusi Nuruddin Ar-Raniri Dalam Tradisi Penulisan Hadis di Nusantara - Ia Mufti Hidayat; Dadah Sa’adah; Dikdik Dahlan Lukman (Yayasan Cendekia Gagayunan Indonesia, 2025)
This study discusses the traces of 17th century hadith scholars with a focus on Nuruddin ar-Raniri, a prominent scholar in the archipelago, and his contribution to the tradition of hadith writing. Nuruddin ar-Raniri, through his work Hidayat al-Ḥabib fī al-Targhib wa-al-Tarhib compiled in 1636 CE, became a pioneer in introducing hadith into the Malay language. The book consists of 831 traditions sourced from Sahih al-Bukhari, Sahih Muslim, and Sunan al-Tirmidzi, which are accompanied by translations and explanations in Malay. This research utilizes a qualitative methodology with a literature study approach and applies the descriptive-analytical method to evaluate the structure, sources, and socio-political influences behind the writing of Hidayat al-Ḥabib. The results show that ar-Raniri played a crucial role in strengthening the tradition of hadith scholarship in Aceh as a center of Islamic scholarship. Although access to his works is still limited, ar-Raniri's contribution to the development of hadith in the archipelago is significant. This study enriches the discourse on the intellectual heritage of Nusantara scholars and their influence in the Islamic hadith tradition in the archipelago.